2021
DOI: 10.1021/acs.inorgchem.1c01402
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Gas and VOC Separation and Pesticide Detection in a Highly Stable Interpenetrated Indium–Organic Framework

Abstract: The new indium-based organic framework {(Me2NH2)­[In­(BDPO)]·DMF·2H2O} n (1) was successfully constructed by using the oxalamide group modified ligand N,N′-bis­(isophthalic acid)­oxalamide (H4BDPO). This framework presents a 2-fold interpenetrating structural characteristic, and the unique polar pore environment leads to a high capture ability for CO2, C2H n and CH3OH and good separation ability for CO2 and C2H n over CH4 as well as for CH3OH over C2H5OH, which was further verified by an ideal adsorbed solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…According to the photo-induced electron transfer (PET) theory, if the lowest unoccupied molecular orbital (LUMO) energy level of the ligand is higher than that of the analyte, the electron transfer occurs between the ligand and the analyte, resulting in the fluorescence quenching. The shapes and relative energy levels of the highest occupied molecular orbital (HOMO) and LUMO of 4-dptb and MEAA were calculated using density functional theory at the B3LYP/6-31G level (Figure and Table S4).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the photo-induced electron transfer (PET) theory, if the lowest unoccupied molecular orbital (LUMO) energy level of the ligand is higher than that of the analyte, the electron transfer occurs between the ligand and the analyte, resulting in the fluorescence quenching. The shapes and relative energy levels of the highest occupied molecular orbital (HOMO) and LUMO of 4-dptb and MEAA were calculated using density functional theory at the B3LYP/6-31G level (Figure and Table S4).…”
Section: Results and Discussionmentioning
confidence: 99%
“…With the addition of 1 mL ethanol, the fluorescence intensity hardly quenched in 3 mL of LCP 1 solvent suspension without MEAA, indicating that the effect of a bare solvent on the sensing function under experimental conditions was negligible (Figure S10). (III) According to the photo-induced electron transfer (PET) theory, 45 if the lowest unoccupied molecular orbital (LUMO) energy level of the ligand is higher than that of the analyte, the electron transfer occurs between the ligand and the analyte, resulting in the fluorescence quenching. The shapes and relative energy levels of the highest occupied molecular orbital (HOMO) and LUMO of 4-dptb and MEAA were calculated using density functional theory at the B3LYP/6-31G level (Figure 7 and Table S4).…”
Section: Fluorescence Sensing Of Meaa For Lcpmentioning
confidence: 99%
“…The limit of detection (LOD) is defined as 3σ/ K sv ( σ is the standard deviation of the blank solution). The calculated detection limits of DCN were 0.0155 ppm for LNU-45 and 0.0197 ppm for LNU-47, which is better than some reported values, such as 0.13 ppm for BPyTPE, 2.93 ppm for (H 3 O)[Zn 2 L(H 2 O)]·3NMP·6H 2 O, 3.85 ppm for {(Me 2 NH 2 )[In(BDPO)]·DMF·2H 2 O} n , 0.212 ppm for 1-L, 0.233 ppm for 3-L, and 0.1753 ppm for DNA-AuNCs [ 1 , 14 , 49 , 50 , 51 ]. The results demonstrated that LNUs could detect trifluralin and dicloran with high selectivity and sensitivity, providing the possibility of detecting residual organic pesticides for practical applications.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of coordinated metal clusters with special structures can be obtained by designing organic ligands and changing the inorganic metal nodes, giving varied functions, 34–36 such as luminescence, magnetism, catalysis, etc. 37–58 Among them, LCMCs have been widely used in the detection of metal ions, nitro explosives and biomolecules because of their well-defined active sites, accurately tailorable structures and excellent luminescent properties, enabling mechanism-based luminescence sensing optimization. 59–65 According to literature studies, there are few reports using LCMCs as luminescence sensors for detecting halide ions or amino acids, especially no bifunctional sensors for halide ions and amino acid determination.…”
Section: Introductionmentioning
confidence: 99%